BIOMETRIA DE FRUTOS E SEMENTES DA CASTANHEIRA-DO-BRASIL DA REGIÃO MÉDIO-NORTE DO MATO GROSSO (Nativa, 2018)
Neste estudo caracterizou-se biometricamente os frutos e as sementes de Bertholletia excelsa Humb. & Bonpl., oriundas dos municípios de Itaúba e Cláudia, MT. As coletas dos frutos de dez matrizes em área de mata nativa ocorreram em 26/11 e 22/12/14 e 10/03/15. Foram coletados todos os frutos no chão sob projeção da copa da matriz. Foram determinadas as seguintes variáveis: diâmetros equatorial e longitudinal do fruto e da semente, espessura do exocarpo e mesocarpo, massa do fruto e das sementes por fruto, número de frutos por planta e número de sementes por fruto. Os frutos apresentaram massa fresca entre 136 e 163 g, diâmetros médios de 34 cm (com exocarpo), espessura total superior a 11 cm (exocarpo + mesocarpo) e 17 sementes por fruto. A massa das sementes de B. excelsa sem tegumento variou de 2,95 a 4,20g. No beneficiamento dos frutos e das sementes da castanheira-do-Brasil na região Médio-Norte, MT, são gerados 68,35% de resíduos. Na safra 14/15, o pico de dispersão dos frutos de B. excelsa ocorreu no mês de dezembro. Coletas tardias de frutos (março) geram baixa qualidade do fruto e da semente.Palavras-chave: Bertholletia excelsa, castanha, produto florestal não-madeireiro, extrativismo. BIOMETRY OF FRUIT AND SEEDS OF BRAZIL CHESTNUT ORIGINITING OF THE MEDIUM-NORTH REGION OF MATO GROSSO STATE ABSTRACT:In this study the fruits and seeds of Bertholletia excelsa Humb. & Bonpl., from the municipalities of Itaúba and Cláudia, MT, were characterized biometrically. The fruits collected from ten matrices in a native forest area. The colletions occurred on 11/26 and 12/22/14 and 10/03/15. All fruits were collected on the ground and under projection of the canopy of the matrix. The following variables were determined: equatorial and longitudinal diameters of fruit and seed, exocarp and mesocarp thickness, fruit and seed mass per fruit, number of fruits per plant and number of seeds per fruit. The fruits presented a fresh mass between 136 and 163 g, average diameters of 34 cm (with exocarp), total thickness superior to 11 cm (exocarp + mesocarp) and 17 seeds per fruit. The seed mass of B. excelsa without tegument ranged from 2.95 to 4.20 g. In the processing of fruits and seeds of Brazilian chestnut in the region of Medium-North, MT, 68.35% of waste is generated. In the 14/15 season, the fruit dispersion peak of B. excelsa occurred in the month of December. Late fruit collections (March) generate poor quality of fruit and seed.Keywords: Bertholletia excelsa, chestnut, non-timber forest product, extractivism. DOI: http://dx.doi.org/10.5935/2318-7670.v05nespa04